Colovaginal and colo-ovarian fistula at a patient with asymptomatic diverticular disease. Issue 4 (26th April 2018) - Syllaios, Athanasios; Koutras, Antonios; Zotos, Prokopis A; Koura, Sofia; Machairoudias, Pavlos; Papakonstantinou, Anastasia; Bourganos, Nikolaos; Liakos, Aristotelis
Abstract: Colovaginal and colo-ovarian fistulas are rare entities that could be attributed to diverticular disease after an episode of acute diverticulitis. Τhey could initially be manifested with symptoms that lead patients to the gynecologist. Gynecologists should consider them in the differential diagnosis, especially after recurrent episodes of sinusitis. We report the case of a 51-year-old woman with a colovaginal and a colo-ovarian fistula due to subclinical diverticular disease, which should be involved in the differential diagnosis in those complicated fistulas, even if the patient had never before a clinical episode of acute diverticulitis or known diverticular disease, and a successful surgical approach.